Ejecución de obras públicas y generación de valor público en el distrito de Chinchao, Huánuco, 2023 - Edyl Alfonso Lizana Minga (Gaceta Científica, 2026)
Objective: Determine in what way the execution of public works influences the generation of public value in the district of Chinchao, Huanuco, Peru, 2023. Materials and methods: The present research corresponds to an applied type of research, with an explanatory level and a non-experimental design. The research had two sample groups: the first consisted of 28 officials and administrative workers of the District Municipality of Chinchao, and the second consisted of 373 inhabitants of the Chinchao district. The survey technique was applied, using the questionnaire as an instrument. To test the formulated hypotheses, descriptive and inferential statistics were applied, and the correlation index was interpreted. Results: The results demonstrate that the execution of public works has a positive, moderate, and significant impact on the generation of public value in the district of Chinchao, Huánuco, Peru, 2023. This is reflected in the Spearman correlation coefficient (r = 0.635) and a p-value of 0.012, lower than the significance level (0.05), indicating that as the execution of public works increases, public value also tends to grow, although not to an extreme extent. Conclusions: It is concluded that the execution of public works had a positive, moderate, and significant influence on the generation of public value in the district of Chinchao, Huanuco, during the year 2023. The results show that greater execution of public works strengthens the public value perceived by the population by improving the provision of goods and services and meeting collective needs. Consequently, efficient and timely management of public works is a fundamental factor in promoting local development and strengthening citizens' confidence in the municipal administration.